Stereochemistry for engineering spin crossover: structures and magnetic properties of a homochiral vs. racemic [Fe(N3O2)(CN)2] complex. Issue 15 (19th March 2015) - Wang, Qiang; Venneri, Shari; Zarrabi, Niloofar; Wang, Hongfeng; Desplanches, Cédric; Létard, Jean-François; Seda, Takele; Pilkington, Melanie
Abstract : The first chiral Fe II complex of an N3 O2 macrocycle comprises of a 1 : 1 mixture of HS and LS states at 250 K and undergoes both a thermal and light induced SCO. Abstract : The Schiff-base condensation of the R, R -(+)-diamine (2a ) with 2, 6-diacetyl pyridine in the presence of Fe II affords the macrocyclic complex [Fe(dpN3 O2 )(CN)2 ] (3a ) (dp = diphenyl) with ligand centred chirality comprising of a 1 : 1 mixture of LS 6- and HS 7-coordinate Fe II centres. Variable temperature magnetic susceptibility and Mössbauer studies reveal that (3a ) undergoes an incomplete thermal SCO transition with a T 1/2 = 250 K as well as a LIESST effect. In contrast its racemic counterpart (3c ) comprises of mostly LS Fe II and exhibits no LIESST properties.